Auditoría de gestión y su impacto en la toma de decisiones en el almacén “Súper Pato” matriz La Maná, provincia Cotopaxi, periodo 2022. - Cedeño Ganchozo, Dayra Michel (2023)
In the present project, a management audit was developed and applied to the "Super Pato" Store, during the period 2022, which had as its motive to identify strengths and weaknesses. To carry out the aforementioned, different research methodologies were used such as bibliographic, field, as well as techniques such as the interview directed to the manager, and observation sheet applied to the company, which was relevant to proceed with the execution of the audit. This examination begins with completing an audit program where the activities to be carried out in each phase are detailed, proceeding with the preliminary phase establishing the main data that the company has as background information. In the planning phase, the reason, objective, scope, resources, and brands to be used are established, likewise, during the execution, the SWOT analysis and the evaluation of internal control questionnaires, the COSO I model are carried out, obtaining a risk level of 14.72. % and confidence level of 85.28%, so; as a result, an audit risk of 0.35% is determined according to the evaluation, thus detecting the findings and indicators signifying that this Store does not effectively and efficiently comply with all the processes. For the communication phase, the audit report was prepared, where the auditor's opinion is shown, detailing all the observations in a clearer and more orderly manner, resulting in the lack of a truly established mission and vision, the non-existence of a manual of functions and the lack of a human talent department, which is why the implementation of a policies and procedures manual is proposed, a document that details the functions and policies for each department in order to improve work performance, the achievement of objectives and proposed goals.